Mengenal Fenomenologi Persepsi Merleau-Ponty tentang Pengalaman Rasa - Sebastian, Tanius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2016)
Phenomenology of Perception is one of the main philosophical works of a France phenomenological philosopher, Maurice Merleau-Ponty. In this book, Merleau-Ponty elaborates his reflection on the nature of the body based on the perception of the world. In “Sense Experience,” which is part of Phenomenology of Perception, explains the bodily experience and its relation to human’s mode of being in the world. This part is important to look upon, for it serves as the basis for Merleau-Ponty’s phenomenological thought on perception. In “Sense Experience”, while affirming his critique on empiricism and intellectualism, Merleau-Ponty also reflects the meaning of sense experience, the unity of the sense, the analytical attitude, the nature of the body, and the ambiguity of sense experience itself. Two key ideas surface from “Sense Experience,” that is, sense experience with and through the body, and bodily experience with and through the world. One might speak of the world, yet one is part of it. It is the body that allows such ambiguity.